10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Background Mobile applications for infectious disease surveillance can facilitate early outbreak detection and timely public health action. However, there is limited information about their real-world adoption, public trust, perceived usefulness, and preferred features. Objective To assess public trust, usability, and adoption of infectious disease surveillance mobile apps and to identify the features preferred by the public. Method An anonymous, online, cross-sectional survey was conducted across Australia between May and August 2024. A total of 5177 adults aged ⩾ 18 years completed the survey. Descriptive statistics and multivariable logistic regression analyses examined sociodemographic correlates of mobile app use, trust, and perceived usefulness. Results Use of infectious disease surveillance apps was low, with only 151 participants (2.9%) reporting prior use. Despite this, 60% (3122/5177) perceived such apps as useful, and 15% (790/5177) reported trust in them. Younger adults were significantly more likely to use and trust these apps than older adults. Occupation in a health-related field (Odds ratio [OR] 1.89; 95% Confidence interval [CI] 1.21, 2.93), frontline responder status (OR 3.33; 95% CI 1.86, 5.96), postgraduate education (OR 2.04; 95% CI 1.20, 3.46), and speaking a non-English language at home (OR 2.72; 95% CI 1.50, 4.91) were significant predictors of app use. Men reported greater trust (OR 1.20; 95% CI 1.01, 1.43) but lower perceived usefulness (OR 0.81; 95% CI 0.72, 0.92) than women. Participants most frequently preferred features providing real-time updates and affected-area maps. Conclusion Although most participants perceived mobile apps to be useful, their adoption was low. Use may vary over time and increase during pandemics, severe epidemics, or travel. Trust diverged from perceived usefulness in specific groups, and sustained use clustered with greater confidence. Design and implementation of infectious disease surveillance apps should emphasise high-value features, language equity, targeted onboarding for older adults, and strategies that convert trust into perceived usefulness.Implications for health information management practice:These findings highlight the need to integrate trust, usability, and accessibility into app design. Prioritising user-centred interfaces, language inclusivity, and transparent data practices in all facets of healthcare services, including the management of health information, can enhance engagement, improve data quality, and support effective digital disease surveillance. The health information manager's skillset would be essential for informing the successful integration of mobile health app data into electronic medical or health record systems.